THE EFFECT OF HABIT IN LISTENING TO ENGLISH SONG TOWARD INDONESIAN STUDENTSâ€™ LISTENING SKILL - Sari, Indah (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 5 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This research purposes to describe the studentsâ€™ listening skill between two habits of listen to English song and to measure comparison of studentsâ€™ listening skill. Ex-post facto was used as method in this research. The population are first gradeof SMAN 4 Kediri. The sample are for about 183 students.The data was taken through test and questionnaire. The results of the research were: (1) the students who usually listen to English song belong to the good category. (2)The students who do not listen to English song belong to the good score. (3)The comparison found out that mean of listening 1 was 68.96 and listening 2 was 63.57. While the value of â€œsignificance of 2-tailelâ€ each variable at the level 1% was 0.00. It means that there is significant difference of listening skill between students who usually listen to English song and do not. The researcher does hope the students more attention toward positive habit of listening to English song to increase listening skill.